Second Generation Biofuels: Economics and Policies - Carriquiry, Miguel A. (2012)
This study reviews economics of production of second generation biofuels from various feedstocks, including crop and wood/forestry residues, lignocellulosic energy crops, jatropha, and algae. The study indicates that while second generation biofuels could significantly contribute to the future energy supply mix, cost is a major barrier to its commercial production in the near to medium term. Depending upon type of biofuels, feedstock prices and conversion costs, the cost of cellulosic ethanol is found to be two to three times higher than the current price of gasoline on an energy equivalent basis. The median cost (across the studies reviewed) of biodiesel produced from microalgae, a prospective feedstock, is seven times higher than the current price of diesel, although much higher cost estimates have been reported. As compared with the case of first generation biofuels, in which feedstock can account for over two-thirds of the total costs, the share of feedstock in the total costs is relatively lower (30-50%) in the case of second generation biofuels. While significant cost reductions are needed for both types of second generation biofuels, the critical barriers are at different steps of the production process. For cellulosic ethanol, the biomass conversion costs needs to be reduced. On the other hand, feedstock cost is the main issue for biodiesel. At present, policy instruments, such as fiscal incentives and consumption mandates have in general not differentiated between the first and second generation biofuels except in the cases of the US and EU. The policy regime should be revised to account for the relative merits of different types of biofuels.